Poética de uma conversão neorromântica: o erotismo religioso de Murilo Mendes - Robson Coelho Tinoco (Estudos de Literatura Brasileira Contemporânea)
The neoromantic poetics of Murilo Mendes (in O visionário, A poesia em pânico and Poesia liberdade) - also composed of a strong erotic-religious component - relies in spiritual-physical aspects that reveal as much as hide, as marks of a unique surrealism. In this poetics, the woman is especially defined between images and allegories built on a thematic basis on which the catholic altar and its multiple meanings (printed on dogmatic faith) complete itself in the curvilinear design of feminine forms (printed on the physical desire). This poetic, presentedas part of the Brazilian literature since 1930, is being built through this neoromanticism - as lyrical as modern - that leads the poet to confront, to question and to discover the world (hisand his women's) as has of lyricism and (in) sensuality, eroticism and (in) religion.